A curcumin derived probe for colorimetric detection of azide ions in water. (21st November 2017) - Adhikari, Susanta; Guria, Subhajit; Ghosh, Avijit; Pal, Abhishek; Das, Debasis
Abstract : A curcumin based probe (CUC-P ) having an active alkyne moiety has been synthesised for selective detection of azide (N3 − ) ions in aqueous medium. Abstract : A curcumin based probe (CUC-P ) having an active alkyne moiety has been synthesised for selective detection of azide (N3 − ) ions in aqueous medium. In the presence or absence of Cu(i )/Cu(ii ) ions, CUC-P visibly changes its colour and fluorescence profile upon addition of N3 − ions, allowing facile discrimination from other common ions. The detection limits for N3 − ions measured using the UV-Vis spectroscopic method and the fluorescence method are 10 μM and 1 μM, respectively. Moreover, the Cu(ii ) complex ofCUC-P shows changes in its colour and emission profile in the presence of N3 − ions more rapidly, making bothCUC-P and its Cu(ii ) complex excellent, highly selective colorimetric probes for N3 − ions. The recognition of N3 − ions may be documented on a paper strip in the solution state and even simply by mechanical grinding in the solid state.